Simplified fuzzy ARTMAP network-based method for assessment of structural damage applied to composite structures. (October 2016) - de Oliveira, Mario A; Inman, Daniel J
This paper addresses a novel method for structural damage assessment based on the electromechanical impedance (EMI) technique applied to composite structures. This method is based on a high-frequency excitation range in order to overcome the difficulties caused when the low vibration modes are excited. A structure made up of unidirectional carbon fiber pre-impregnated with resin-epoxy is excited using a chirp signal which varies the frequency in a wide range through the PZT (Lead Zirconate Titanate) patches. From the structural response signal, the Euclidean Distance (ED) is computed from each structural condition considering the pristine condition as a reference (baseline). The ED is used as input to the Simplified Fuzzy ARTMAP Network (SFAN) which is responsible for identifying various different structural conditions. It is shown that the robustness provided by SFAN allows the evaluation of the progress of structural damage even under critical conditions. The structural damage was simulated by loosening bolts in a structure. Furthermore, the repaired condition was also considered by retightening bolts. The paper discusses the advantages and drawbacks of the approach in light of the experimental results.